Membrane topology of three Xcp proteins involved in exoprotein transport by Pseudomonas aeruginosa. - Bleves, S (1996)
Xcp proteins constitute the secretory apparatus of Pseudomonas aeruginosa. Deduced amino acid sequence of xcp genes, expression, and subcellular localization revealed unexpected features. Indeed, most Xcp proteins are found in the cytoplasmic membrane although xcp mutations lead to periplasmic accumulation of exoproteins, indicating that the limiting step is translocation across the outer membrane. To understand the mechanism by which the machinery functions and the interactions between its components, it is valuable to know their membrane organization. We report data demonstrating the N(in)-C(out) topologies of three general secretion pathway components, the XcpP, -Y, and -Z proteins.